Engaging end-users to inform the development of the global standard for the identification of key biodiversity areas. Issue 89 (November 2018) - Maxwell, Jessica; Allen, Simon; Brooks, Thomas; Cuttelod, Annabelle; Dudley, Nigel; Fisher, Janet; Langhammer, Penny; Patenaude, Genevieve; Woodley, Stephen
Highlights: End-user input informed the development of a new global conservation standard. Revealed remarkable convergence in end-user opinion on many topics. End-user opinions diverged on scale, cost, prioritisation, and development activities. Process led to establishment of the KBA Consultative Forum for sustained engagement. Five good practice recommendations proposed for successful end-user engagement. Abstract: We report results from an end-user engagement process, convened by the International Union for Conservation of Nature (IUCN), which informed the development of the Global Standard for the Identification of Key Biodiversity Areas. Key Biodiversity Areas are sites contributing significantly to the global persistence of biodiversity. We used a mixed methods approach involving interviews and an online questionnaire with end-users to determine their needs and concerns in relation to the Key Biodiversity Area approach. We found a remarkable level of convergence in end-user opinion on 12 important topics. Four topics resulted in a divergence in end-user opinion requiring further dialogue and consideration, including: (i) the value of a global standard compared to various national approaches; (ii) the prioritisation of Key Biodiversity Areas over other areas; (iii) whether Key Biodiversity Area data should be made freely available; and (iv) whether or not development activities should be permitted in Key Biodiversity Areas. Our results informed the development of the Global Standard for the Identification of Key Biodiversity Areas and a new governance structure, the Key Biodiversity Area Consultative Forum, which provides a mechanism for ongoing dialogue with end-users. We conclude by sharing five good practice recommendations for future end-user engagement processes.